2019
DOI: 10.1111/apt.15306
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: association between Helicobacter pylori CagA seropositivity and odds of inflammatory bowel disease

Abstract: Background: Accumulating data support a protective role of Helicobacter pylori against inflammatory bowel diseases (IBD), which might be mediated by strain-specific constituents, specifically cagA expression. Aim:To perform a systematic review and meta-analysis to more clearly define the association between CagA seropositivity and IBD. Methods:We identified comparative studies that included sufficient detail to determine the odds or risk of IBD, Crohn's disease (CD) or ulcerative colitis (UC) amongst individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 60 publications
2
50
0
Order By: Relevance
“…49 associated with an increased IBD risk. 50 These data support a likely protective effect of H pylori on IBD as reported by other meta-analyses, [51][52][53] possibly caused by the bacterium's ability to promote immune system maturation and prevent the onset of aberrant immune responses. Indeed, H pylori exerts immunomodulatory effects by increasing the number of regulatory T cells, which suppress excessive inflammatory T-cell responses through the secretion of IL-10 and TGF-β.…”
Section: Infl Ammatory Bowel D Is E a S Esupporting
confidence: 80%
“…49 associated with an increased IBD risk. 50 These data support a likely protective effect of H pylori on IBD as reported by other meta-analyses, [51][52][53] possibly caused by the bacterium's ability to promote immune system maturation and prevent the onset of aberrant immune responses. Indeed, H pylori exerts immunomodulatory effects by increasing the number of regulatory T cells, which suppress excessive inflammatory T-cell responses through the secretion of IL-10 and TGF-β.…”
Section: Infl Ammatory Bowel D Is E a S Esupporting
confidence: 80%
“…By affecting immune and inflammatory responses [ 78 , 92 , 431 , 432 , 433 ]. HPI may protect against asthma and allergy (particularly in children), autoimmune disorders (systemic lupus erythematosus, rheumatoid arthritis [RA] and multiple sclerosis, coeliac disease), inflammatory bowel disease (especially Crohn’s disease), eosinophilic esophagitis, eczema, obesity [ 9 , 78 , 342 , 433 , 434 , 435 , 436 , 437 , 438 , 439 , 440 , 441 ] and tooth loss [ 442 ]. Negative associations between these diseases and HPI (beneficial effects) were observed mainly in patients colonized with cagA+ strains of H.p.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Previous meta-analyses have suggested that the beneficial effects of H. pylori on the risk of IBD are greater for eastern than for western populations [ 16 ]. A possible explanation is the greater relative abundance of the seropositive CagA H. pylori strain in East Asian compared to western populations [ 23 ]. It has been suggested that expression of CagA might increase the production of beta-defensins, thought to play a protective role in IBD pathogenesis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is the greater relative abundance of the seropositive CagA H. pylori strain in East Asian compared to western populations [ 23 ]. It has been suggested that expression of CagA might increase the production of beta-defensins, thought to play a protective role in IBD pathogenesis [ 23 ]. Another possible theory is that during H. pylori infection, the response of the type 2 T helper cell 2 (Th2) cytokine is dependent on the presence of CagA strain [ 23 ].…”
Section: Discussionmentioning
confidence: 99%